Thomas' railway word book - Britt, Allcroft (New york : Random house, 2000)
Thomas and his friends introduce words that pertain to the world of trains.
"based on the railway series by the Rev. W. Awdry"
Keywords: Railroad-- trains--fiction; Vocabulary